Achieving strength-ductility synergy in cold spray additively manufactured Al/B4C composites through a hybrid post-deposition treatment. Issue 6 (June 2019) - Tariq, Naeem ul Haq; Gyansah, Lawrence; Qiu, Xiang; Jia, Chunni; Awais, Hasan Bin; Zheng, Chengwu; Du, Hao; Wang, Jiqiang; Xiong, Tianying
Abstract: Cold spray additive manufacturing (CSAM) provides a potential solid state manufacturing route to fabricate variety of aluminum matrix composites (AMCs) with reduced possibility of undesired chemical reactions and residual thermal stresses. This study presents a hybrid (i.e. hot compression + hot rolling) post-deposition treatment to reinvigorate the mechanical properties of cold spray additively manufactured Al/B4 C composites. The as-deposited samples were initially subjected to 30% thickness reduction via hot compression treatment at ∼500 °C followed by a hot rolling treatment with 40% thickness reduction in 2 passes. Electron backscatter diffraction (EBSD) and high resolution transmission electron microscopy (HRTEM) results revealed that after hybrid post-deposition treatment (involving 70% accumulative thickness reduction), the aluminum grains in the matrix were extensively refined due to simultaneous operation of continuous dynamic recrystallization (CDRX) and geometric dynamic recrystallization (GDRX). Furthermore, interfacial defects were remarkably reduced while the nature of Al/Al and Al/B4 C interfacial bonding was changed from sheer mechanical interlocking to metallurgical bonding which facilitated efficient transference of applied load to uniformly dispersed bimodal B4 C particles. As a result, ultimate tensile strength (UTS) and elongation (EL) of the as-deposited sample were simultaneously improved from ∼37 to 185 MPa and ∼0.3% to 6.2%, respectively.